Pegadaian Syariah dalam Tinjauan Konseptual - Nurmala Nurmala; Damayanti Damayanti; Rusmianto Rusmianto (Jurnal Ilmiah ESAI, 2010)
This review discusses what sharia pawnshop is and its legal basis, therefore this review can be used as reference and give satisfaction for those who will have transaction in sharia pawnshop. Further, people will choose sharia pawnshop as trusted financial institution to increase their prosperity.Key words : Sharia Pownshop